2016
DOI: 10.1002/mnfr.201600162
|View full text |Cite
|
Sign up to set email alerts
|

Green tea (-)-epigallocatechin-3-gallate counteracts daytime overeating induced by high-fat diet in mice

Abstract: Our study demonstrates that EGCG supplement specifically counteracts daytime overeating induced by HFD in mice, suggesting its central role in regulating feeding behavior and energy homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Diminished insulin signaling in the brain has an orexigenic effect, which results in body weight gain associated with peripheral insulin resistance (66). Furthermore, a high-fat diet was reported to impair the brain reward system and propagate a vicious cycle of repetitive eating (67). In this study, the effect of HFFD on the expression of appetite-regulating genes was in agreement with previous reports, and EGCG was found to attenuate this effect.…”
Section: Discussionsupporting
confidence: 92%
“…Diminished insulin signaling in the brain has an orexigenic effect, which results in body weight gain associated with peripheral insulin resistance (66). Furthermore, a high-fat diet was reported to impair the brain reward system and propagate a vicious cycle of repetitive eating (67). In this study, the effect of HFFD on the expression of appetite-regulating genes was in agreement with previous reports, and EGCG was found to attenuate this effect.…”
Section: Discussionsupporting
confidence: 92%
“…Polyphenols, such as proanthocyanidins, resveratrol, and nobiletin have drawn increasing attention as their clock‐enhancing properties. A recent research exhibited that supplementary of EGCG altered diurnally oscillating expression pattern of key appetite‐regulating genes as well as key circadian genes like Clock and Bmal1 in hypothalamus of mice . Furthermore, our previous studies have revealed that EGCG, the most abundant catechin in green tea, may ameliorate HFFD‐induced obesity and metabolic disorders via circadian clock related mechanisms .…”
Section: Discussionmentioning
confidence: 96%
“…Huang et al [40] showed that Jiao-Tai-Wan could increase the expression levels of circadian proteins CRY1 and CRY2 in hypothalamus of obesity-resistant rats with chronic partial sleep deprivation, which was associated with improvement in inflammation. The benefits of green tea (-)-epigallocatechin-3-gallate on food intake were confirmed to be associated with the expression of Clock and Bmal1 in hypothalamus of high-fat fed mice [41]. However, research exploring the association between the protective effects of genistein intake against metabolic disorders and the circadian clock is scarce.…”
Section: Discussionmentioning
confidence: 99%